MANAJEMEN PONDOK PESANTREN DALAM PENGEMBANGAN MUTU PENDIDIKAN DI PONDOK PESANTREN DARUSSALAM BLOKAGUNG BANYUWANGI - Shodiq, Ahmad Shodiq Pratama (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2023)
In educational institutions, quality is one of the barometers used by consumers in viewing all aspects that are in educational institutions, from which consumers can determine whether the educational institution is in accordance with the desired needs or not. Good quality is needed by educational institutions when they want to continue to exist, in reality education is required to always improve quality in accordance with the development of information technology. Included in this is that Islamic boarding schools as Islamic educational institutions must also oversee current technological advances with good moral guidance, thus the role of Islamic boarding schools is very important in maintaining the nation's moral values. This study aims to find out how the Darussalam Blokagung Islamic Boarding School improves the quality of its education. This research used qualitative research. Data collection was carried out using interview and observation techniques. In this study, descriptive analysis was used as a tool to explore broader data related to Pondok Pesantren Darussalam. The research results obtained were that the management of educational quality planning at the Darussalam Blokagung Islamic Boarding School was in accordance with several quality boarding school education requirements with the advantages of collaboration between the general education curriculum and the pesantren curriculum. Key words : Quality management, education, pesantren.